Analysis of Government Policy Regarding the Quality of Education and Its Implications for the Progress of Islamic Religious Education in Indonesia - Imam Musthofa; Helmiati; Hariza Hasyim (Al-Ard: Journal of Education, 2025)
This study aims to analyze the Indonesian government’s policies to improve education quality and their implications for the advancement of Islamic education. Over the past two decades, education quality has become a central issue in the national education system, especially following the implementation of various policies such as the National Education Standards (SNP), the Education Quality Assurance System (SPMP), teacher certification, professional education programs (PPG), and the Merdeka Belajar–Kampus Merdeka initiative. This study employs a qualitative descriptive method using a library research approach through the analysis of legal documents, ministerial reports, books, and scholarly journals published between 2019 and 2025. The findings indicate that government policies to improve education quality have significantly contributed to strengthening Islamic education systems in both public and religious schools. Curriculum reform, teacher professionalism, and the digitalization of madrasahs have become key drivers in Islamic education development. However, implementation challenges persist, including regional quality disparities, limited human resources, and uneven institutional capacity. Therefore, synergy between the Ministry of Education and the Ministry of Religious Affairs is essential to establish an integrated quality assurance system consistent with Islamic values.